La participación parental en el proceso de aprendizaje en los niños de la Escuela “Antonio Frías”. - Yasig Jácome, Ana Fabiola (2021)
The priority in the educational field is the integral training of students so they become people with values who are capable of living daily lives. To achieve this, the participation of family is imperative because the affective ties motivate learning. Nevertheless, each time it is difficult for parents to get involved with the pedagogical process due to different factors and as a result students' learning decreases because they do not have the support of their parents and because parents do not devote time to their children. So, parental participation in the educational process help improve communication among parents, students and teachers. In such a manner, the objective of research work is to reinforce parental participation through fun strategies in the learning process of students from "Antonio Frías" school. The methodology is based on the quantitative approach, the survey as a technique and the questionnaire as the instrument which allowed to gather information related to the variables of the object of study. Results reflected the lack of interest that parents have in the school activities from the institution as well as the children academic performance. Therefore, this project contributes with a proposal that is focused on fun strategies to reinforce the interpersonal connections between parents and children so as to achieve a better involvement from parents in children education, so the beneficiaries and students and parents.